How Will Capitalism End?: Essays on a Failing System - Streeck, Wolfgang (Verso Books, 2016)
The provocative political thinker asks if it will be with a bang or a whimperAfter years of ill health, capitalism is now in a critical condition. Growth has given way to stagnation; inequality is leading to instability; and confidence in the money economy has all but evaporated.In How Will Capitalism End?, the acclaimed analyst of contemporary politics and economics Wolfgang Streeck argues that the world is about to change. The marriage between democracy and capitalism, ill-suited partners brought together in the shadow of World War Two, is coming to an end. The regulatory institutions that once restrained the financial sector’s excesses have collapsed and, after the final victory of capitalism at the end of the Cold War, there is no political agency capable of rolling back the liberalization of the markets.Ours has become a world defined by declining growth, oligarchic rule, a shrinking public sphere, institutional corruption and international anarchy, and no cure to these ills is at hand.
Sociology; Political Science
Keywords: political science / globalization; political science / political economy; political science / political ideologies / democracy

Karl Polanyi: The Hungarian Writings - Dale, Gareth (Oxford University Press, 2016)
The work of Karl Polanyi has gained in influence in recent years to become a point of reference to a wide range of leading authors in the fields of economics, politics, sociology, and social policy. The volume is a combination of reflections on, and assessment of, the nature of Polanyi's contribution and new strands of work, both theoretical and empirical, that has been inspired by Polanyi's insights. It gathers together the key contributions to the first ever workshop on the work of Karl Polanyi held in the United Kingdom. The workshop was opened by Kari Polanyi-Levitt, who also has written the Introductory Foreword to this book. Several of the contributions develop Polanyian ideas in relation to contemporary capitalism. However, in a critical spirit, other contributions in the volume substantially transform his concept 'instituted economic process' in considering a broad range of contemporary socio-economic change: markets for mobile telephony, call centre operations, and European labour markets.
Political Science
Keywords: history - modern; political history; political philosophy; political theory

Karl Polanyi: A Life on the Left - Dale, Gareth (Columbia University Press, 2016)
Karl Polanyi (1886–1964) was one of the twentieth century's most original interpreters of the market economy. His penetrating analysis of globalization's disruptions and the Great Depression's underlying causes still serves as an effective counterargument to free market fundamentalism. This biography shows how the major personal and historical events of his life transformed him from a bourgeois radical into a Christian socialist but also informed his ambivalent stance on social democracy, communism, the New Deal, and the shifting intellectual scene of postwar America.The book begins with Polanyi's childhood in the Habsburg Empire and his involvement with the Great War and Hungary's postwar revolution. It connects Polanyi's idealistic radicalism to the political promise and intellectual ferment of Red Vienna and the horror of fascism. The narrative revisits Polanyi's oeuvre in English, German, and Hungarian, includes exhaustive research in five archives, and features interviews with Polanyi's daughter, students, and colleagues, clarifying the contradictory aspects of the thinker's work. These personal accounts also shed light on Polanyi's connections to scholars, Christians, atheists, journalists, hot and cold warriors, and socialists of all stripes. Karl Polanyi: A Life on the Left engages with Polanyi's biography as a reflection and condensation of extraordinary times. It highlights the historical ruptures, tensions, and upheavals that the thinker sought to capture and comprehend and, in telling his story, engages with the intellectual and political history of a turbulent epoch.
History
Keywords: European history; biography; history - Europe / Austria & Hungary; history - United States / 20th Century; history - modern; history - modern / 20th Century; social science; sociology

The Commonalities of Global Crises: Markets, Communities and Nostalgia - Karner, Christian; Weicht, Bernhard (Springer, 2016)
Bringing together contributions from an international group of social scientists, this collection examines diverse crises, both historical and contemporary, which implicate market forces, widening inequalities, social exclusion, forms of resistance, and ideological polarisation. The Commonalities of Global Crises offers carefully researched case studies which stretch across large geographical distances- from Egypt to the US and from northern, central, eastern and southern Europe to South America- and covers timely issues including human rights, slavery, care, migration, racism, and the far right. The volume demonstrates that such different settings and diverse concerns are characterized by a common tension in which the crises that unfold around pressures of widening marketization and commodification are met by the (re)building or re-assertion of various communities, and competing politics of solidarity and nostalgia.
Sociology; Political Science
Keywords: business & economics / general; commodification; disembedding; double movement; economic theory; political science / general; social science / general

From Keynes to Piketty: The Century that Shook Up Economics - Haan, Peter de (Springer, 2016)
From Keynes to Piketty provides the reader with an accessible and entertaining insight into the development of economic thought over the past century. Starting with John Maynard Keynes's bestseller, The Economic Consequences of Peace (1919), and ending with Thomas Piketty's blockbuster, Capital in the Twenty First Century (2014), the author explains which dramatic political and economic events changed the way economists interpreted these events, and how they revolutionized the economic science.The book contains biographies of Keynes, Schumpeter, Galbraith, Hayek, Friedman, Hirschman, North, and Piketty, alongside others, and highlights their extraordinary lives and works, anecdotes about them, and their often sharp differences of opinion. Extensive summaries of their main works provide the interested scholar and student with an accurate presentation of their contents. A must-read for all those who wonder what happened to economics during the past century, and why.
Economics
Keywords: KEYNES; John Maynard; 1883-1946; PIKETTY; Thomas; business & economics; economic history

Bourgeois Equality: How Ideas, Not Capital or Institutions, Enriched the World - McCloskey, Deirdre N. (University of Chicago Press, 2016)
There’s little doubt that most humans today are better off than their forebears. Stunningly so, the economist and historian Deirdre McCloskey argues in the concluding volume of her trilogy celebrating the oft-derided virtues of the bourgeoisie. The poorest of humanity, McCloskey shows, will soon be joining the comparative riches of Japan and Sweden and Botswana. Why? Most economists—from Adam Smith and Karl Marx to Thomas Piketty—say the Great Enrichment since 1800 came from accumulated capital. McCloskey disagrees, fiercely. “Our riches,” she argues, “were made not by piling brick on brick, bank balance on bank balance, but by piling idea on idea.” Capital was necessary, but so was the presence of oxygen. It was ideas, not matter, that drove “trade-tested betterment.” Nor were institutions the drivers. The World Bank orthodoxy of “add institutions and stir” doesn’t work, and didn’t. McCloskey builds a powerful case for the initiating role of ideas—ideas for electric motors and free elections, of course, but more deeply the bizarre and liberal ideas of equal liberty and dignity for ordinary folk. Liberalism arose from theological and political revolutions in northwest Europe, yielding a unique respect for betterment and its practitioners, and upending ancient hierarchies. Commoners were encouraged to have a go, and the bourgeoisie took up the Bourgeois Deal, and we were all enriched. Few economists or historians write like McCloskey—her ability to invest the facts of economic history with the urgency of a novel, or of a leading case at law, is unmatched. She summarizes modern economics and modern economic history with verve and lucidity, yet sees through to the really big scientific conclusion. Not matter, but ideas. Big books don’t come any more ambitious, or captivating, than Bourgeois Equality. KM - Part IV heavily engages with Polanyi's ideas, including embeddedness
Economics; Political Science
Keywords: Europe; business & economics; economic history; embeddedness; history; political science; political theory; social science

The Great Acceleration: An Environmental History of the Anthropocene since 1945 - McNeill, J. R. (Harvard University Press, 2016)
The pace of energy use, greenhouse gas emissions, and population growth has thrust the planet into a new age—the Anthropocene. Humans have altered the planet’s biogeochemical systems without consciously managing them. The Great Acceleration explains the causes, consequences, and uncertainties of this massive uncontrolled experiment.
History; Political Science
Keywords: anthropocene; history / modern / 20th Century; history / world; nature / environmental conservation & protection; political science / public policy / environmental policy

England's Great Transformation: Law, Labor, and the Industrial Revolution - Steinberg, Marc W. (University of Chicago Press, 2016)
With England’s Great Transformation, Marc W. Steinberg throws a wrench into our understanding of the English Industrial Revolution, largely revising the thesis at heart of Karl Polanyi’s landmark The Great Transformation. The conventional wisdom has been that in the nineteenth century, England quickly moved toward a modern labor market where workers were free to shift from employer to employer in response to market signals. Expanding on recent historical research, Steinberg finds to the contrary that labor contracts, centered on insidious master-servant laws, allowed employers and legal institutions to work in tandem to keep employees in line. Building his argument on three case studies—the Hanley pottery industry, Hull fisheries, and Redditch needlemakers—Steinberg employs both local and national analyses to emphasize the ways in which these master-servant laws allowed employers to use the criminal prosecutions of workers to maintain control of their labor force. Steinberg provides a fresh perspective on the dynamics of labor control and class power, integrating the complex pathways of Marxism, historical institutionalism, and feminism, and giving readers a subtle yet revelatory new understanding of workplace control and power during England’s Industrial Revolution.
History; Economics; Sociology
Keywords: business & economics / economic history; economic history; history / Europe / Great Britain; history / general; industrial revolution; social science / sociology / general

Ireland, Small Open Economies and European Integration: Lost in Transition - Begg, David (International Political Economy Series., 2016)
Presents a development model for the recovery of the Irish polity post-2008 financial crisis and traces and compares the evolution of the development models of Finland, Denmark, the Netherlands, and Ireland from 1987 to 2012, considering how those four countries managed the process of Europeanization. Explores the core Polanyian tension between markets and social protection, with particular reference to the capacity of selected small, open economies to manage that tension as compared with Ireland. Discusses the world of Peter J. Katzenstein–the major historical events that contributed to the formation of the polities of Denmark, Finland, the Netherlands, and Ireland, as well as how the development models evolved as European integration intensified; 1994-2001–the age of employment miracles; 2001-08–European integration intensifies; going beyond 2008–coping with the crisis; and unpacking Ireland's polity from a new institutionalist perspective. Begg is Director of the Think Tank for Action on Social Change and former General Secretary of the Irish Congress of Trade Unions. Bibliography; index.
Economics
Keywords: current heterodox approaches: historical; economic integration; evolutionary; heterodox economics; institutional; international institutional arrangements; international political economy; open economy macroeconomics; political processes: rent-seeking; lobbying; elections; legislatures; social protection; voting behavior

Reconstructing Karl Polanyi - Dale, Gareth (Pluto Press, 2016)
Karl Polanyi was one of the most influential political economists of the twentieth-century and is widely regarded as the most gifted of social democrat theorists. In Reconstructing Karl Polanyi, Gareth Dale draws upon primary sources archived in the countries that Polanyi called home—Hungary, Austria, Britain, the United States, and Canada—to provide a sweeping survey of his contribution to the social sciences. Polanyi’s intellectual and political outlook can best be summarized through paradoxical formulations such as ‘romantic modernist’, ‘liberal socialist’, and ‘cosmopolitan patriot.’ In exploring these paradoxes, Dale excavates and reconstructs Polanyi’s views on a range of topics that have been neglected in the critical literature, including Keynesian economic policy, the evolution and dynamics of Stalin’s Russia, regional integration, and McCarthyism. He reinterprets Polanyi’s philosophy of history, his theory of democracy, and his economic historiography of Ancient Greece and Mesopotamia, and guides readers through Polyani's critical dialogue with Marxism. While the central threads and motifs of this study are intellectual-historiographical in nature, Dale also critically analyzes the views of Polanyi and his followers on issues of pressing present-day relevance, notably the clash between democracy and capitalism, and the nature and trajectory of European unification.
Political Science
Keywords: political theory; social theory

Economics as Social Science: Economics imperialism and the challenge of interdisciplinarity - Marchionatti, Roberto; Cedrini, Mario (Taylor & Francis, 2016)
There is a growing consensus in social sciences that there is a need for interdisciplinary research on the complexity of human behavior. At an age of crisis for both the economy and economic theory, economics is called upon to fruitfully cooperate with contiguous social disciplines. The term ‘economics imperialism’ refers to the expansion of economics to territories that lie outside the traditional domain of the discipline. Its critics argue that in starting with the assumption of maximizing behaviour, economics excludes the nuances of rival disciplines and has problems in interpreting real-world phenomena. This book focuses on a territory that persists to be largely intractable using the postulates of economics: that of primitive societies. In retracing the origins of economics imperialism back to the birth of the discipline, this volume argues that it offers a reductionist interpretation that is poor in interpretative power. By engaging with the neglected traditions of sociological and anthropological studies, the analysis offers suggestions for a more democratic cooperation between the social sciences. Economics as Social Science is of great interest to those who study history of economic thought, political economy and the history of economic anthropology, as well as history of social sciences and economic methodology.
Keywords: economic theory; economics imperialism